Crisientia Pranata Raharja STRATEGI PEMBERDAYAAN MASYARAKAT BERBASIS EKONOMI KREATIF: STUDI KASUS KAIAKAIU BRAND - Crisientia Pranata Raharja; Juanita Priscilla (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2020)
Indonesia has entered the era of the creative economy. Various local brands began to be increasingly known.This gave rise to increasingly fierce competition. Micro, Small and Medium Enterprises, or MSMEs, are increasinglyemerging and are supported by regional and government regulations. But for some people, it feltvery heavy. Individual business forms are increasingly pressured to survive in industrial competition. The lackof knowledge about government programs and the right strategy makes industry players unable to developtheir businesses. This paper will give you the strategy to increase individual business with KAIAKAIU as thecase study. KAIAKAIU is a new local brand, in collaboration with the locals. Creating a product that couldmake the people contribute to Indonesian society. The approach uses SWOT (Strength, Weakness, Opportunityand Threat) and Business Model Canvas using community approaches. The research is aimed at exploringappropriate strategies for competing in the ASEAN Economic Community (AEC), especially for the micro andindividual industries.